Unscrambling variation in avian eggshell colour and patterning in a continent-wide study. Issue 1 (30th January 2019) - L'Herpiniere, Kiara L.; O'Neill, Louis G.; Russell, Andrew F.; Duursma, Daisy Englert; Griffith, Simon C.
Abstract : The evolutionary drivers underlying marked variation in the pigmentation of eggs within many avian species remains unclear. The leading hypotheses proposed to explain such variation advocate the roles of genetic differences, signalling and/or structural integrity. One means of testing among these hypotheses is to capitalize on museum collections of eggs obtained throughout a broad geographical range of a species to ensure sufficient variation in predictors pertaining to each hypothesis. Here, we measured coloration and patterning in eggs from 272 clutches of Australian magpies ( Cracticus tibicen ) collected across most of their geographical range of ca 7 million km 2 ; encompassing eight subspecies, variation in environmental parameters, and the presence/absence of a brood parasite. We found considerable variation in background colour, as well as in the extent and distribution of patterning across eggs. There was little evidence that this variation was explained by subspecies or the contemporary presence of a brood parasite. However, measures of maximum temperature, leaf area index and soil calcium all contributed to variation in egg appearance, although their explanatory power was relatively low. Our results suggest that multiple factors combine to influence egg appearance in this species, and that even in species with highly variable eggs, coloration is not readily explained.